An annotated check-list of genera and species of carpoids. Lista anotada de los géneros y especies de carpoideos - Dominguez Alonso, Patricio; Jefferies, Richard P.S.; Gil Cid, Dolores (Coloquios de Paleontología, 2002)
This check-list includes the at present valid names of genera and species of the carpoids. It is a provisional attemp to stabilize the names of all formally described carpoids up to date and includes most of the combinations of genera and species that have been used in the scientific literature. It should be especially useful to those reading older papers in which a wide variety of genera and species have been used, and to those interested in biodiversity, evolutionary studies or history of the palaeontology. The check-list is divided into five sections: 1. Index of genera; II. Index of species; III Index of valid specific epithets; IV. Tables of stratigraphical occurrence